Molecular characterization, localization, and physiological roles of ITP and ITP-L in the mosquito, Aedes aegypti - Sajadi, Farwa; Paluzzi, Jean-Paul V. (Frontiers in Insect Science, 2024)
The insect ion transport peptide (ITP) and its alternatively spliced variant, ITP-like peptide (ITP-L), belong to the crustacean hyperglycemic hormone family of peptides and are widely conserved among insect species. While limited, studies have characterized the ITP/ITP-L signaling system within insects, and putative functions including regulation of ion and fluid transport, ovarian maturation, and thirst/excretion have been proposed. Herein, we aimed to molecularly investigate Itp and Itp-l expression profiles in the mosquito, Aedes aegypti, examine peptide immunolocalization and distribution within the adult central nervous system, and elucidate physiological roles for these neuropeptides. Transcript expression profiles of both AedaeItp and AedaeItp-l revealed distinct enrichment patterns in adults, with AedaeItp expressed in the brain and AedaeItp-l expression predominantly within the abdominal ganglia. Immunohistochemical analysis within the central nervous system revealed expression of AedaeITP peptide in a number of cells in the brain and in the terminal ganglion. Comparatively, AedaeITP-L peptide was localized solely within the pre-terminal abdominal ganglia of the central nervous system. Interestingly, prolonged desiccation stress caused upregulation of AedaeItp and AedaeItp-l levels in adult mosquitoes, suggesting possible functional roles in water conservation and feeding-related activities. RNAi-mediated knockdown of AedaeItp caused an increase in urine excretion, while knockdown of both AedaeItp and AedaeItp-l reduced blood feeding and egg-laying in females as well as hindered egg viability, suggesting roles in reproductive physiology and behaviour. Altogether, this study identifies AedaeITP and AedaeITP-L as key pleiotropic hormones, regulating various critical physiological processes in the disease vector, A. aegypti.